Pengaruh kemampuan literasi informasi siswa SMA Negeri 1 Sorkam Barat terhadap kesadaran informasi akan berita hoax - Fitriyani Lubis; Abdul Karim Batubara (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Because of the growing widespread use of the internet, every individual, including students, must be able to recognise and identify hoax news circulating, and each one must have information literacy abilities to prevent it. The purpose of this study is to examine the information literacy skills of SMA Negeri 1 Sorkam Barat pupils in terms of hoax news awareness. A survey method using a quantitative approach was adopted. A questionnaire was utilised as the study instrument, and basic linear regression was used to analyse the data. This study's population consists of 943 students from SMA Negeri 1 Sorkam Barat. The samples were drawn from the slovin calculation results, which included 90 pupils. This study's variables are students' information literacy abilities (X) and information awareness of hoax news (Y). The study's findings indicate that literacy skills have an impact on information awareness of false news. The regression findings demonstrate that the X variable has an influence on Y, with a significant value of 0.000 0.05 and a tcount of 3.971 > ttable 1.991. A constant of 13,192 denotes the constant value of variable X. Because the coefficient is positive, we can deduce that literacy skills are strong, so will information awareness of hoax news